CULTURAL POLITICS OF EX-NONMAINSTREAM RELIGIOUS MOVEMENTS MUHDI AKBAR IN THE SELAYAR ISLANDS - Saehu, Rahmat; Syamsul, Andi; Eko Putro, Moh. Zaenal Abidin (Al-Qalam, 2024)
Non-mainstream religious movements are a characteristic feature of island regions isolated by the sea. This movement first existed as a societal need at that time. This article attempts to answer the question of how a community of ex-nonmainstream religious movements carries out cultural politics to survive amid the increasingly dominant mainstream religion. This study is based on interview data and observations conducted on several informants. Movement history manuscripts are also a secondary data source in this research. Objectively, it was found that the ex-Muhdi Akbar community carried out cultural politics in three forms. First, they reoriented their movement from focusing on religion and politics to social and cultural ones. Second, open membership regulations and freedom in choosing an official religion means they have a higher emotional bond. Third, accommodation in the government strengthens their position as religious people and does not deviate so that the problems they previously experienced can be minimized. This form of cultural politics is a formula for the success of a non-mainstream religious movement.